Is there still a case for merchant interconnectors? Insights from an analysis of welfare and distributional aspects of options for network expansion in the Baltic Sea region - Clemens Gerbaulet; Alexander Weber (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Despite the ongoing appetite of financial investors for merchant investments into the European electricity network, the EC is reluctant to approve such undertakings, thus implicitly favoring regulated investments. Based on a two-level model, we analyze the impact of profit-maximizing merchant transmission investment as compared to welfare-maximizing regulated transmission investment. We apply the model to the Baltic Sea region, which has in the past been subject to rapid interconnector development and still would benefit from increased interconnection. We obtain stable results indicating that merchant investment may well contribute to overall welfare, but at the same time, "the merchant takes it all", i.e. in many cases merchant profits are close to the overall efficiency gain, and sometimes even higher. These results underline that that distributional aspects, besides mere welfare arguments should be taken into account when analyzing the impact of merchant transmission investment.
Keywords: L51; L94; D30; D60; 330; Merchant; Regulated; Transmission Expansion; MPEC